Reporting disease activity in clinical trials of patients with rheumatoid arthritis: EULAR/ACR collaborative recommendations. Issue 10 (12th September 2008) - Aletaha, D; Landewe, R; Karonitsch, T; Bathon, J; Boers, M; Bombardier, C; Bombardieri, S; Choi, H; Combe, B; Dougados, M; Emery, P; Gomez-Reino, J; et al.
Abstract : Objective: To make recommendations on how to report disease activity in clinical trials of rheumatoid arthritis (RA) endorsed by the European League Against Rheumatism (EULAR) and the American College of Rheumatology (ACR). Methods: The project followed the EULAR standardised operating procedures, which use a three-step approach: (1) expert-based definition of relevant research questions (November 2006); (2) systematic literature search (November 2006 to May 2007); and (3) expert consensus on recommendations based on the literature search results (May 2007). In addition, since this is the first joint EULAR/ACR publication on recommendations, an extra step included a meeting with an ACR panel to approve the recommendations elaborated by the expert group (August 2007). Results: Eleven relevant questions were identified for the literature search. Based on the evidence from the literature the expert panel recommended that each trial should report the following items: (1) disease activity response and disease activity states; (2) appropriate descriptive statistics of the baseline, the endpoints and change of the single variables included in the core set; (3) baseline disease activity levels (in general); (4) the percentage of patients achieving a low disease activity state and remission; (5) time to onset of the primary outcome; (6) sustainability of the primary outcome; (7) fatigue. Conclusions: These recommendations endorsed by EULAR and ACR will help harmonise the presentations of results from clinical trials. Adherence to these recommendations will provide the readership of clinical trials with more details of important outcomes, while the higher level of homogeneity may facilitate the comparison of outcomes across different trials and pooling of trial results, such as in meta-analyses.